Weight loss-associated superior mesenteric artery syndrome, an unusual condition in a peruvian patient: a case report - Chirinos, Luis A. (2018)
Superior mesenteric artery syndrome (SMAS) is an uncommon cause of small bowel obstruction. We report a young male patient with abdominal pain, emesis and history of significant weight loss. Computed tomography angiography demonstrated narrowing of the aortomesenteric angle. The patient underwent conservative medical management, focusing on relieving obstruction and nutritional support.